Flipping Leadership Doesn't Mean Reinventing the Wheel. - DeWitt, Peter M. (Corwin connected educators series., 2014)
Flip communication for instant impact-and real results for students. The Corwin Connected Educator series is your key to unlocking the greatest resource available to all educators: other educators. With this volume, you'll use the principles of connectedness and flipped learning to engage stakeholders-teachers, administrators, and parents-digitally, so they're ready for productive discussion when you meet in person. Featuring action steps, reflections, and "connected moments," plus more resources online, the book shows you how flipped leadership Makes the school community visible to parent.